Evolution of hot rolling texture in pure tungsten and lanthanum oxide doped tungsten with various reductions. (5th November 2016) - Zhang, Xiaoxin; Yan, Qingzhi; Lang, Shaoting; Wang, Yijia; Ge, Changchun
Abstract: Textures of hot rolled pure tungsten (PW) and W-1.0 wt%La2 O3 (W-1%La2 O3 ) with various strains were characterized to figure out the effect of rolling reduction and second phase on evolution of hot rolling texture. Initial sintering texture of 〈111〉//ND and 110〈111〉, 112〈111〉 slip systems as well as dynamic recovery, dynamic recrystallization facilitated the formation of the θ-fiber and γ-fiber textures for PW and W-1%La2 O3 during the hot rolling process. Furthermore, dynamic recovery occurred in 72% rolled PW and 43% rolled W-1%La2 O3 led to a significant rise of 001〈110〉 texture. Besides, dynamic recrystallization occurred in 80% rolled PW and 72% rolled W-1%La2 O3 resulted in an enhancement of 001 〈100〉 accompanied with a drop of 111 〈112〉 texture. The occurrence of dynamic recovery and dynamic recrystallization in W-1%La2 O3 was sooner than in PW, which may be caused by more dislocations in total and additional geometrically necessary dislocations as well as local deformation zone induced by adding of La2 O3 particles. Graphical abstract: Highlights: Hot rolled PW and W-1%La2 O3 with various strains displayed θ-fiber and γ-fiber textures simultaneously Dynamic recovery in 72% rolled PW, 43% rolled W-1%La2 O3 improved 001〈110〉 texture Dynamic recrystallization in 80% rolled PW, 72% rolled W-1%La2 O3 improved 001〈100〉 texture and reduced 111〈112〉 texture Occurrence of dynamic recovery and dynamic recrystallization in W-1%La2 O3 was sooner than in PW